The Effect of Education and Unemployment on Poverty in Indonesia's 34 Provinces (2018–2023): The Mediating Role of the Human Development Index - Fayza, Salsabila; Sinambela, Rut Afentina; Situmorang, Rachel Meylani; Nafisha, Nadya; Silaban, Putri Sari Margaret Julianty (Jurnal Ekonomi Balance, 2025)
This study investigates the impact of education and unemployment on poverty across Indonesia’s 34 provinces from 2018 to 2023, with the Human Development Index (HDI) serving as a mediating variable. Using secondary panel data and employing path analysis within a fixed effect model framework, the research explores both direct and indirect relationships among variables. The results indicate that unemployment significantly and negatively affects HDI, while education significantly and positively influences HDI. Furthermore, HDI has a significant negative impact on poverty, demonstrating its mediating role in reducing poverty through improvements in education. However, education does not directly influence poverty in a statistically significant manner. In contrast, unemployment directly and positively influences poverty levels. The Sobel test confirms that HDI significantly mediates the effect of education on poverty, but does not mediate the relationship between unemployment and poverty. These findings suggest that enhancing human capital through education can reduce poverty indirectly by improving HDI. However, addressing unemployment requires targeted labor market interventions, as improvements in HDI alone are insufficient to mitigate poverty caused by joblessness. The study underscores the importance of integrated policy approaches that simultaneously enhance education quality and employment opportunities to effectively reduce poverty and promote inclusive development in Indonesia.